Long-term results of intensity-modulated radiotherapy with three dose-fractionation regimens for localized prostate cancer - Takemoto, Shinya (J Radiat Res, 2019)
We evaluated long-term outcomes of three protocols of intensity-modulated radiation therapy (IMRT) for localized prostate cancer. Between 2005 and 2014, 348 patients were treated with 5-field IMRT. The first 74 patients were treated with a daily fraction of 2.0 Gy to 74 Gy (low-risk prostate cancer) or 78 Gy (intermediate- or high-risk prostate cancer); then 101 patients were treated with 2.1-Gy daily fractions to 73.5 or 77.7 Gy. More recently, 173 patients were treated with 2.2-Gy fractions to 72.6 or 74.8 Gy. The median age of all patients was 70 years and the median follow-up period was 82 months. The median follow-up periods were 124 months in the 2.0-Gy group, 98 months in the 2.1-Gy group, and 69 months in the 2.2-Gy group. The overall and prostate-specific antigen (PSA) failure-free survival (PSA-FFS) rates were, respectively, 89 and 68% at 10 years for the 2.0-Gy group, 91 and 84% at 8 years for the 2.1-Gy group, and 93 and 92% at 6 years for the 2.2-Gy group. The PSA-FFS rate for high-risk patients in all groups was 80% at 7 years. The cumulative incidences of Grade ≥2 late genitourinary (GU) and gastrointestinal (GI) toxicity were, respectively, 7.2 and 12.4% at 10 years for the 2.0-Gy group, 7.4 and 14.1% at 8 years for the 2.1-Gy group, and 7.1 and 7.9% at 6 years for the 2.2-Gy group. All three fractionation schedules yielded good tumor control with acceptable toxicities.